Dynamic changes in the mitochondrial electron transport chain underpinning cold acclimation of leaf respiration - ARMSTRONG, ANNA F; BADGER, MURRAY R; DAY, DAVID A; BARTHET, MICHELLE M; SMITH, PENELOPE M.C; MILLAR, A. HARVEY; WHELAN, JIM; ATKIN, OWEN K (Plant, cell and environment, 2008)
We examined the effect of short- and long-term changes in temperature on gene expression, protein abundance, and the activity of the alternative oxidase and cytochrome oxidase pathways (AOP and COP, respectively) in Arabidopsis thaliana. The AOP was more sensitive to short-term changes in temperature than the COP, with partitioning to the AOP decreasing significantly below a threshold temperature of 20 °C. AOP activity was increased in leaves, which had been shifted to the cold for several days, but this response was transient, with AOP activity subsiding (and COP activity increasing) following the development of leaves in the cold. The transient increase in AOP activity in 10-d cold-shifted leaves was not associated with an increase in alternative oxidase (AOX) protein or AOX1a transcript abundance. By contrast, the amount of uncoupling protein was significantly increased in cold-developed leaves. In conjunction with this, transcript levels of the uncoupling protein-encoding gene UCP1 and the external NAD(P)H dehydrogenase-encoding gene NDB2 exhibited sustained increases following growth in the cold. The data suggest a role for each of these alternative non-phosphorylating bypasses of mitochondrial electron transport at different points in time following exposure to cold, with increased AOP activity being important only in the early stages of cold treatment.